2017
DOI: 10.12693/aphyspola.132.451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Techniques for Fetal Heart Rate Classification

Abstract: Cardiotocography is a monitoring technique providing important and vital information on fetal status during antepartum and intrapartum periods. The advances in modern obstetric practice allowed many robust and reliable machine learning techniques to be utilized in classifying fetal heart rate signals. The role of machine learning approaches in diagnosing diseases is becoming increasingly essential and intertwined. The main aim of the present study is to determine the most efficient machine learning technique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…He didn't apply simulation for his results or provide hybrid models for improving classification accuracy rate. Z. Cömert [12] presented the comparative metrics of five www.ijacsa.thesai.org machine learning techniques such as Artificial Neural Network (ANN) [1, 2, and 13], support vector machine [14], extreme learning machine [15], radial basis function network [16] and random forest [17]. He found that ANN technique is the most efficient in the sensitivity and specificity measures.…”
Section: Introductionmentioning
confidence: 99%
“…He didn't apply simulation for his results or provide hybrid models for improving classification accuracy rate. Z. Cömert [12] presented the comparative metrics of five www.ijacsa.thesai.org machine learning techniques such as Artificial Neural Network (ANN) [1, 2, and 13], support vector machine [14], extreme learning machine [15], radial basis function network [16] and random forest [17]. He found that ANN technique is the most efficient in the sensitivity and specificity measures.…”
Section: Introductionmentioning
confidence: 99%
“…In the text preprocessing, using “Word to Vector” as “ n -gram” algorithm and taking advantage of Zemberek library increased rates of success to find word roots. We use the evaluations metrics which are precision, sensitivity, F-measure, and accuracy [ 55 , 56 ]. These metrics are depending on TP (true-positive) and FP (false-positive) ratios: …”
Section: Resultsmentioning
confidence: 99%
“…The evaluation result is an assessment using a formula by comparing the portion of data that is correctly classified and the portion of data that is misclassified [18]. Table 2 showed the evaluation result using accuracy, precision, and recall.…”
Section: Evaluation Resultsmentioning
confidence: 99%